PRZEPISY OGÓLNE PRAWA ADMINISTRACYJNEGO I DEFINIOWANIE POJĘĆ - Zimmermann, Jan (Wydział Prawa i Administracji UAM, 2009)
The twenty years o f transformations in Poland are a good opportunity for proposing some ways in which the condition of Polish administrative law could be improved. One of the recommended actions is formulation o f general provisions of that branch of law. There two basic ways in which such an act could be drafted and substantially passed. A minimalist action would be to add to the existing system the missing elements, thus consolidating the system without any modification or intervention. Alternatively, the “general part” of administrative law could be created. A way to do that would be first, to identify, and next, to extract from it those elements or provisions that are of general character, and subsequently encapsulate them in one separate normative act. The definition o f the basic legal concepts of administrative law is of fundamental importance and several groups of such concepts may be identified. The first one includes concepts for which a statutory definition seems indispensable. In the first place this applies to concepts from the administrative law system that establish the mutual relationships between the administering subjects. The second one includes those concepts for which a statutory definition is at least disputable. To those belong concepts like an organ of public administration, or, in particular, concepts of individual forms o f the public administration activity. The necessity of defining an administrative decision produces some controversies as well. The third and last group includes those concepts, the defining of which seems to be out of the question. This includes, first of all, the concept of administrative recognition as defined in the draft bill on general provisions of administrative law which is the main subject of analysis in this paper. Defining general clauses, especially those of public interest, is also unacceptable.
GENERAL PROVISIONS OF ADMINISTRATIVE LAW AND DEFINING CONCEPTS